Interaction between dopamine and octopamine in Drosophila melanogaster brain - Magalam, Raghavendra (2014)
Dopamine and octopamine, a possible analogue of noradrenaline, are among a few neurotransmitters which play a crucial role in several physiological processes. Dopamine participates in learning, memory and in reward, whereas, octopamine participates in egg laying, fight and flight response and also exhorts aggressive behaviour. Researchers had demonstrated that dopaminergic signalling can act antagonistic to octopamine in Caenorhabditis elegans. When C. elegans was fed, it exhibit sleep and reward emotions, due to the production of Dopamine. Conversely, when animals were subjected to fasting, they have produced octopamine, by suppressing dopamine signalling, and this lead to CREB activation, which eventually resulted in longevity of C. elegans (Suo et al.2009). These observations illustrate the need to investigate the dopamine and octopamine interactions and their effects on longevity in another model organism, Drosophila melanogaster. To carry out my investigation, two dopamine receptors (DopR1 and DopR2) in octopaminergic neurons (neurons where their primary transmitter is octopamine) were knocked down and the insect’s social behaviour as well as longevity was monitored. Based upon my study, I conclude that the cessation of dopamine receptors may not result in longevity of D. melanogaster, instead the starvation resistance of DopR2 knockdown flies was reduced when compared to DopR1 knockdown flies and wild type flies. However, it was observed that DopR2 knockdown flies showed increased aggressive behaviour, decreased male-male courtship and reduced activity when compared to wild type flies.